Visual methodologies : an introduction to researching with materials - Rose, Gillian Cathryn, 1962- (London : SAGE Publications, 2016)
Now in its Fourth Edition, Visual Methodologies: An Introduction to Researching with Visual Methodologies is a bestselling critical guide to the study and analysis of visual culture. Existing chapters have been fully updated to offer a rigorous examination and demonstration of an individual methodology in a clear and structured style. Reflecting changes in the way society consumes and creates its visual content, new features include: * Brand new chapters dealing with social media platforms, the development of digital methods and the modern circulation and audiencing of research images * More 'Focus' features covering interactive documentaries, digital story-telling and participant mapping * A Companion Website featuring links to useful further resources relating to each chapter. A now classic text, Visual Methodologies appeals to undergraduates, graduates, researchers and academics across the social sciences and humanities who are looking to get to grips with the complex debates and ideas in visual analysis and interpretation.
Keywords: Visual culture; Social Media; Visuele communicatie